The City of Banda Aceh's planning and budgeting in regional work units: Are they gender responsive? - Ulfa, Widya; Zainuddin, Muslim; Khalil, Zakki Fuad; Muazzinah, Muazzinah; Nashriyah, Nashriyah (Universitas Islam Negeri Ar-Raniry, 2022)
Gender Responsive Planning and Budgeting (PPRG) is an instrument to overcome the gap in access, participation, control and benefits between women and men in the implementation of development to realize a more equitable budget. The implementation of the PPRG policy in every Banda Aceh City Apparatus Work Unit (SKPK) is still lacking in scope so that development from a gender perspective cannot be realized properly. This study aims to examine how the process and mechanism of PPRG and to find out the inhibiting factors in the Banda Aceh SKPK based on the Banda Aceh Mayor Regulations No. 18 of 2018 concerning Guidelines for the Implementation of PPRG for SKPKs. Using a qualitative method with a descriptive approach to examine primary data obtained by interview and observation techniques and secondary data by literature. The results show that the process of implementing the PPRG in the Banda Aceh SKPK only began with the issuance of policies as the legal regulation for implementation, provision of disaggregated data and technical guidelines. Then the stage of socialization and assistance in the preparation of the PPRG which produces examples of GAP and GBS where these two things are tools for integrating gender in planning documents. The inhibiting factors are the limitations of human resources and budget, there is no strong pressure in leadership, employee transfers to changes in nomenclature.